Pengendalian Kurs Rupiah Terhadap Dollar Amerika Serikat Melalui Suku Bunga SBI = Rupiah Against US Dollar Exchange Rate Control Through SBI Discount Rate - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Changing on Indonesian exchange rate system from fixed to dirty floating system since August 14, 1997, had made rupiah against US dollar rate fluctuating freely and achieved its higher rate on June 1998 at Rp I4,900/USD. Sharp depreciation of Indonesian exchange rate, like ones on 1998 and on late 2000, raised again the issue whether policy makers should raise Indonesian domestic interest rate if the exchange rate depreciated or the FED had a plan to raise its future discount rate, or let its value would be determined by market mechanism. Opinions said that Bank Indonesia as monetary authority in Indonesia should intervene by raising its discount rate based on an understanding that interest rate should be raised until its value was competitive enough relative to interest rate abroad so exchange rate depreciated could be stopped or its magnitude could be avoided. This thesis studies the problem in controlling rupiah's exchange rate against US dollar through Bank Indonesia's SBI discount rate. The result was SBI discount rate 1 mount capable in controlling rupiah's exchange rate against US dollar for the period being observed. 90.476% sample of observation of exchange rate growth could be controlled by SBI discount rate one month